Multivalent S2 subunit vaccines provide broad protection against Clade 1 sarbecoviruses in female mice - Peter J. Halfmann; Raj S. Patel; Kathryn Loeffler; Atsuhiro Yasuhara; Lee-Ann Van De Velde; Jie E. Yang; Jordan Chervin; Chloe Troxell; Min Huang; Naiying Zheng; Elizabeth R. Wright; Paul G. Thomas; et al. (Nature Communications)
Abstract The continuing emergence of immune evasive SARS-CoV-2 variants and the previous SARS-CoV-1 outbreak collectively underscore the need for broadly protective sarbecovirus vaccines. Targeting the conserved S2 subunit of SARS-CoV-2 is a particularly promising approach to elicit broad protection. Here, we describe a nanoparticle vaccine displaying multiple copies of the SARS-CoV-1 S2 subunit. This vaccine alone, or as a cocktail with a SARS-CoV-2 S2 subunit vaccine, protects female transgenic K18-hACE2 mice from challenges with Omicron subvariant XBB as well as several sarbecoviruses identified as having pandemic potential including the bat sarbecovirus WIV1, BANAL-236, and a pangolin sarbecovirus. Challenge studies in female Fc-γ receptor knockout mice reveal that antibody-based cellular effector mechanisms play a role in protection elicited by these vaccines. These results demonstrate that our S2-based vaccines provide broad protection against clade 1 sarbecoviruses and offer insight into the mechanistic basis for protection.